The Role Of Local Loan Institution In Providing Safety Net In Rural Area (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2018)
Rural area cannot be separated with poverty, according to Statistics Center Board (BPS), there are 18 milions rural people live below poverty line. Rural poverty has become many focus in development studies. There is a siginificant difference between rural poverty and urban poverty. Poor society in urban area are more vulnurable compared to poor society in rural area. In rural area, poor people tends to have informal social security that helps them to survive. This research aimed to determine the role of loan institution in providing social safety net for rural poor. Qualitative method was used to help us to have a better understanding about the debt institution in rural areas. This research found that rural poor have several alternatives source of debt that enable them to survive in a vulnerable situation. Most of people tend to see for a realistic loan institution with low interest (without interest is more preferable), low risk in returning the debt and fast in providing the money.